2015
DOI: 10.1016/j.ultsonch.2015.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonic cavitation on the diffusivity of a point defect in the passive film on formed Nb in 0.5 M HCl solution

Abstract: This work primarily focused on the influence of ultrasonic cavitation on the transport property of the point defect in the passive film on formed Nb in 0.5M HCl solution via electrochemical techniques based on the point defect model (PDM). The influence of ultrasonic cavitation on the composition and structure of the passive film was detected by X-ray photoelectron spectroscopy (XPS) and Auger electron spectroscopy (AES). The transport property of a point defect in the passive film was characterized by the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…It can be seen that the Mott-Schottky plots can be decomposed into two linear regions over the entire potential range, and the slopes of two linear regions in each plot are always positive, which is characteristics of n-type semiconductors behavior. Such two linear regions located at low and high potentials have also been reported for other metal oxides in different media [46,47,48]. This phenomenon was attributed to a transition of passive film character from semiconducting behavior to dielectric behavior, as discussed in our recent work [49].…”
Section: Resultssupporting
confidence: 81%
“…It can be seen that the Mott-Schottky plots can be decomposed into two linear regions over the entire potential range, and the slopes of two linear regions in each plot are always positive, which is characteristics of n-type semiconductors behavior. Such two linear regions located at low and high potentials have also been reported for other metal oxides in different media [46,47,48]. This phenomenon was attributed to a transition of passive film character from semiconducting behavior to dielectric behavior, as discussed in our recent work [49].…”
Section: Resultssupporting
confidence: 81%
“…There have been many reports about the formation of defects by either or both of these effects, such as oxygen vacancies in metal oxides by ultrasonic treatment (e.g., SiO 2 , , Nb 2 O 5 , MoO 3 , ZnO, ZrO 2 , Fe 2 O 3 , SnO 2 ). In particular, Osorio-Vargas et al showed that oxygen vacancies are formed during low-frequency US treatment of TiO 2 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…This is largely ascribed to the protective effect of the passivation film (Ref 36). Essentially, the electrochemical tests documented in (Ref [37][38][39] prove unanimously that electrochemical properties of the passivation film formed due to ultrasonic cavitation differ considerably from those of the film produced in quiescent liquid. Moreover, the passivation film can improve the resistance to cavitation erosion, as confirmed in (Ref 40).…”
Section: Surface Morphologymentioning
confidence: 99%